Doradca – próba określenia sensu jego roli - Nasreen , Hawari (Studia Edukacyjne, 2017)
In the professional literature regarding the various aspects of the nature on counseling, two terms that define the work of the school counselor stand out in particular: guidance and counseling (Kligman, 1990). The role of the educational counselor could be defined as a unique individual contact which purpose is to promote change and growth in three aspects: personal development, social adjustment and professional development. By this definition, counseling is perceived as a dynamic process characterized by the change in the consultee (Kligman, 1990). Educational counseling is meant to advance the emotional, cognitive and social development of the pupil population in the education system, and to lead the construction of an environment that allows for mental well-being for those growing in it, Educational counseling is aimed to assist the student as an individual, and to the school as a social-organizational system, to reach maximum functionality and to best extract their capabilities from emotional well-being in a supportive and accepting environment (Shefi, Psychilogical Counseling Service (Shefi) policy issue: Work as a Consultant in early childhood, 2002). The counselor is the system’s mental well-being go-to man. His availability inside the school faculty allows him to assist both the individual and the environment, to take the best actions whilst rapidly responding to the student, the faculty and the parents. His location as a faculty member enables him to simultaneously see various, and sometimes opposite, needs of all the target audiences, and to hold a balanced perspective on regulation, to arbitrate and mediate opposite stances. The counselor is a liaison with a systematic viewpoint from inside the school and between the school and the community. His professional purpose regards the entire student population whilst taking into account their various needs and the obligated response these variation dictate.